2003
DOI: 10.1016/s0885-3924(03)00257-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of pain, uncertainty, and hope in Taiwanese lung cancer patients

Abstract: The impact of cancer pain on the quality of life of lung cancer patients is obvious, but the relationship of cancer pain to uncertainty and level of hope in cancer patients is not clear and has been the subject of only a few studies. The purpose of this study is to look at the relationship of pain to uncertainty and hope in Taiwanese lung cancer patients. A crosssectional and descriptive correlational design was used in this study. A convenience sample of lung cancer patients was recruited from chest medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
2
10

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 28 publications
5
68
2
10
Order By: Relevance
“…Similarly, a study of surrogate decision-makers for patients receiving mechanical ventilation revealed that 93% of surrogates considered avoidance of discussions about prognosis to be an unacceptable way to maintain hope. 34 Others have reported that uncertainty about one' s medical situation can result in a diminished sense of hope 35 ; this research argues for the therapeutic power of information, even if it represents bad news. Adult patients with endstage renal disease, for example, felt more empowered about their own medical decisions and more hopeful when they received prognostic information.…”
Section: Benefits Of Prognosis Communication: What Is the Evidence?mentioning
confidence: 89%
“…Similarly, a study of surrogate decision-makers for patients receiving mechanical ventilation revealed that 93% of surrogates considered avoidance of discussions about prognosis to be an unacceptable way to maintain hope. 34 Others have reported that uncertainty about one' s medical situation can result in a diminished sense of hope 35 ; this research argues for the therapeutic power of information, even if it represents bad news. Adult patients with endstage renal disease, for example, felt more empowered about their own medical decisions and more hopeful when they received prognostic information.…”
Section: Benefits Of Prognosis Communication: What Is the Evidence?mentioning
confidence: 89%
“…In relation to kidney transplantation, the great demand for it may be explained by the meaning attributed to the procedure by a large part of patients who believe it will cure their renal disease (15) . Nonetheless, the number of patients included on the kidney transplant waiting list is larger than the number of those who in fact …”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous work that suggests that uncertainty often underlies distress, and that information, even when difficult, can allay one's worst fears. 29,30 This situation may best be remedied, not by altering the nature of the research, but by helping parents to access the information they need.…”
Section: Discussionmentioning
confidence: 99%